Hubungan Perilaku Terhadap Kejadian Computer Vision Syndrome Pada Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Semarang - Putri, Feby Ananda; Martiningsih, Wahju Ratna; Kurniati, Ika Dyah (CV. Publikasi Indonesia, 2025)
CVS is a physical disorder that often occurs, one of which is in the eye where there is a combination of eye complaints with a duration of more than 4 hours without any rest breaks. Computer use without rest breaks can cause several eye complaints such as headaches, back pain, blurred vision, dry eyes, the sensation of burning or burning eyes, and red eyes. The factors that influence the incidence of CVS include women who are more susceptible to CVS, sitting or lying positions, distance <40 cm, and use of contact lenses or contact lenses. COVID 2019 requires learning to be done online. The purpose of this study was to determine the factors associated with CVS in students of the Faculty of Medicine, University of Muhammadiyah Semarang. Research method: this research is observational analytic research with a cross-sectional method. This study uses a questionnaire and a lux meter as instruments or measuring devices to obtain research data. The number of samples from this study was 81 students. The test data used to process the data are Chi-Square and Rank-Spearman. . Research Results: There is a relationship between CVS and the sitting position as indicated by p 0.018. There is a relationship between the distance from the eye to the screen which is shown with a p-value of 0.004. But there is no relationship between screen brightness and CVS as indicated by the p-value of 1.000 (p>0.05). Conclusion: Factors related to CVS are sitting position and distance from using a laptop, while factors not related to CVS are screen brightness